Phase-interface-anchored cadmium single-atom catalysts for efficient methanol steam reforming - Shunan Zhang; Haozhi Zhou; Zilong Shao; Baohuan Wei; Zhen Hu; Hao Liang; Ruonan Zhang; Xiaofang Liu; Hu Luo; Lin Xia; Yuhan Sun; Hui Wang (Nature Communications)
Abstract Employing interface engineering to design innovative single-atom catalysts (SACs) for effective methanol steam reforming (MSR) presents an attractive yet formidable challenge. Here, we report phase-interface confined Cd/P25 SACs, where Cd atoms are stably anchored at the phase interface between anatase (101) and rutile (110) facets. The Cd-O-Ti phase interface sites formed exhibit asymmetric geometric and electronic properties that enable 100% methanol conversion, a low CO concentration (~0.1 mol%) in the effluent gas, and sustained stability exceeding 150 h. The H2 production rate at these interface sites is approximately 15-fold and 8-fold higher than that of anatase and rutile surface sites, respectively. Enhancing the phase interface density through atmosphere pretreatment can further increase the H2 production rate by an additional 11%. Furthermore, these powder SACs can be 3D printed into kilogram-scale monolithic catalysts, advancing practical in-situ hydrogen generation applications.